KEBERADAAN HUKUM ADAT DALAM YURISPRUDENSI - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2016)
The Existance of Customary Law in national legal sistem was finding a important and strategic place and therefore constitutionally recognized in chapter 18 B verse 2 in second changes UUD 1945 with the certain requirements that is as long as the law and these customary law society still alive and in accordance with society development and the principle of NKRI. A confession Customary Law in legal law sistem can be viewed in various statutory regulation formal and specific pointedly, through the adjudication in court pratices that called with Jurisprudence. In Development history of Jurisprudence within Judicial practice in Indonesia can be seen the presence of common law as a form invention of law what does conducted by a judge against any lawsuit besides was the implementation of common law that living and evolving in the certain common law society environment. Keywords: customary law, jurisprudence